2020
DOI: 10.1063/1.5143297
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film flip-chip UVB LEDs realized by electrochemical etching

Abstract: We demonstrate a thin-film flip-chip (TFFC) light-emitting diode (LED) emitting in the ultraviolet B (UVB) at 311 nm, where substrate removal has been achieved by electrochemical etching of a sacrificial Al0.37Ga0.63N layer. The electroluminescence spectrum of the TFFC LED corresponds well to the as-grown LED structure, showing no sign of degradation of structural and optical properties by electrochemical etching. This is achieved by a proper epitaxial design of the sacrificial layer and the etch stop layers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“… 29 31 An alternative way to remove the substrate is to use Al-content- and doping-selective electrochemical etching of AlGaN, which has recently been demonstrated by our groups. 32 , 33 This method allows for the fabrication of AlGaN membranes with high Al content, smooth surfaces, and well-defined thicknesses. Owing to these properties, the membranes can be used for a wide variety of thin-film devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 29 31 An alternative way to remove the substrate is to use Al-content- and doping-selective electrochemical etching of AlGaN, which has recently been demonstrated by our groups. 32 , 33 This method allows for the fabrication of AlGaN membranes with high Al content, smooth surfaces, and well-defined thicknesses. Owing to these properties, the membranes can be used for a wide variety of thin-film devices.…”
mentioning
confidence: 99%
“…Furthermore, the exposed surface must be smooth to avoid scattering losses. Unfortunately, for AlGaN-based devices, substrate removal by laser-induced lift-off can lead to cracking of epitaxial layers and to rough surfaces with root-mean-square roughness of 20 nm or higher, while chemical–mechanical polishing offers poor thickness control. An alternative way to remove the substrate is to use Al-content- and doping-selective electrochemical etching of AlGaN, which has recently been demonstrated by our groups. , This method allows for the fabrication of AlGaN membranes with high Al content, smooth surfaces, and well-defined thicknesses. Owing to these properties, the membranes can be used for a wide variety of thin-film devices.…”
mentioning
confidence: 99%
“…In contrast, electro-chemical etching (ECE) as a well controllable approach is gaining considerable interest within the nitride device community in recent times [ 25 27 ]. For instance, ECE has the potential for selective lateral etching of certain sacrificial nitride layers in the realization of thin film flip-chip LEDs [ 26 ], freestanding devices or III-nitride membranes [ 27 29 ], etc. Recently, it has been reported that the GaN-based LED membranes with a complete device structure from the Si substrate could be achieved by ECE of highly conductive AlN/Si interface [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The UVB LED with a p-side, transparent to the emitted light is grown on top of a sacrificial multilayer (a 118 nm thick Al 0.37 Ga 0.63 N layer and a five-period structure of alternating 5 nm thick Al 0.11 Ga 0.89 N and 5 nm thick Al 0.37 Ga 0.63 N), which is used to separate processed LED devices from the substrate later in the process. That multilayer is embedded between two etch block layers (uid and low-doped Al 0.50 Ga 0.50 N) to confine the electrochemical etching and prevent parasitic etching . The integration of a low-Al-content and high n-doping in the multilayer in combination with the unintentional doping of the top etch block layer and a Si concentration that is lower than that of the sacrificial layer, in this case 2 × 10 18 cm –3 in the n-side of the LED, maximizes the etching selectivity.…”
mentioning
confidence: 99%
“…17 Recently, we have shown an alternative method for the substrate removal, namely selective lateral electrochemical etching of AlGaN sacrificial layers 18 and realized a proof-ofconcept TFFC UVB LED. 19 However, in these devices the ncontact was deposited after electrochemical etching to prevent the contact from being attacked during the electrochemical etching. This prevented annealing of the n-contact which resulted in poor IV-characteristics.…”
mentioning
confidence: 99%